2005
DOI: 10.1016/j.bios.2004.09.027
|View full text |Cite
|
Sign up to set email alerts
|

APDS: the autonomous pathogen detection system

Abstract: We have developed and tested a fully autonomous pathogen detection system (APDS) capable of continuously monitoring the environment for airborne biological threat agents. The system was developed to provide early warning to civilians in the event of a bioterrorism incident and can be used at high profile events for short-term, intensive monitoring or in major public buildings or transportation nodes for long-term monitoring. The APDS is completely automated, offering continuous aerosol sampling, in-line sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 23 publications
0
39
0
2
Order By: Relevance
“…The most sophisticated platform autonomously conducts water filtration, DNA extraction, and genetic assays while deployed and transmits data via satellite (Preston et al 2011). Surveillance of airborne biological hazards has motivated similar developments (Hindson et al 2005), and engineers have also demonstrated use of unmanned aerial systems (i.e. 'drones') to remotely collect water samples (Ore et al 2015).…”
Section: Remote and Autonomous Sampling And Analysismentioning
confidence: 99%
“…The most sophisticated platform autonomously conducts water filtration, DNA extraction, and genetic assays while deployed and transmits data via satellite (Preston et al 2011). Surveillance of airborne biological hazards has motivated similar developments (Hindson et al 2005), and engineers have also demonstrated use of unmanned aerial systems (i.e. 'drones') to remotely collect water samples (Ore et al 2015).…”
Section: Remote and Autonomous Sampling And Analysismentioning
confidence: 99%
“…Quantitative real-time PCR (QPCR) allows not only the identification of collected species, but also their quantification, once proper standard (calibration) curves have been prepared. The conventional QPCR has been incorporated into bioaerosol detection systems, such as the APDS (Hindson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An example in which the Luminex® beads are used to enable an integrated and portable pathogen sensing instrument has recently been demonstrated in a system known as Autonomous Pathogen Detection System (APDS). [16][17][18][19] Subsequent improvements to the APDS system enabled rapid PCR genetic analysis of the antigen and wireless transmission of the obtained flow cytometry and PCR data to a remote/centralized location. 17,19 As illustrated in Fig 2b, the APDS system contains an aerosol collector to constantly "inhale" particles from its surrounding environment for analysis.…”
Section: Microbead-based Immunoassay Sensing Systemmentioning
confidence: 99%
“…[16][17][18][19] Subsequent improvements to the APDS system enabled rapid PCR genetic analysis of the antigen and wireless transmission of the obtained flow cytometry and PCR data to a remote/centralized location. 17,19 As illustrated in Fig 2b, the APDS system contains an aerosol collector to constantly "inhale" particles from its surrounding environment for analysis. It is essential that samples be appropriately prefiltered and pre-concentrated to enable sensitive and accurate pathogen detection.…”
Section: Microbead-based Immunoassay Sensing Systemmentioning
confidence: 99%